Manajemen Tenaga Pendidik dan Kependidikan - Salsabila, Alfania Mahya; Diningrum, Ike Janu Arya; Iskarim, Mochamad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Education is a vital aspect of life that requires effective management to achieve success. Educational personnel management, particularly in the context of Islamic Education, plays a strategic role in managing educational personnel to create an effective learning environment and support holistic student development. This study adopts a qualitative descriptive approach using a literature review method to elucidate the practices and strategies of educational personnel management in Islamic education. Findings indicate that workforce planning, recruitment, training, promotion, and evaluation are crucial aspects of educational personnel management. Effective management ensures that educators can manage learning by understanding student characteristics and utilizing appropriate methods and resources. Additionally, adaptation to changing student needs and the implementation of innovative educational technology are also critical components of educational personnel management in supporting effective learning. Thus, effective educational personnel management in Islamic Education institutions significantly impacts the quality of teaching and learning experiences and overall student development.